2020
DOI: 10.1107/s1600577520008929
|View full text |Cite
|
Sign up to set email alerts
|

On-demand correction for X-ray response non-uniformity in microstrip detectors by a data-driven approach

Abstract: A statistical approach, which was previously developed to correct scattering data for X-ray response non-uniformity (XRNU) in microstrip detectors, has been improved to significantly reduce the correcting time. The improved algorithm has succeeded in increasing the utilization rate of data acquired for reference intensity to 98%. As a result, the correcting time was reduced from half a day to half an hour, which was shorter than the typical measuring time of a sample. Moreover, the present approach was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…The flat-field parameters provided by the manufacturer failed in correcting XRNU. Recently, a data-driven approach, ReLiEf (response-to-light effector) (Kato et al, 2019;Kato & Shigeta, 2020), was developed to restore the detector system to the original dynamic range. ReLiEf has been successfully applied to a total scattering measurement system, OHGI (overlapped high-grade intelligencer) (Kato et al, 2019), which can cover a 2 range from 3 to 156 with a step of 0.01 at the same time by placing 15 MYTHEN modules without a gap between modules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flat-field parameters provided by the manufacturer failed in correcting XRNU. Recently, a data-driven approach, ReLiEf (response-to-light effector) (Kato et al, 2019;Kato & Shigeta, 2020), was developed to restore the detector system to the original dynamic range. ReLiEf has been successfully applied to a total scattering measurement system, OHGI (overlapped high-grade intelligencer) (Kato et al, 2019), which can cover a 2 range from 3 to 156 with a step of 0.01 at the same time by placing 15 MYTHEN modules without a gap between modules.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we assess the quality of structural parameters and ED modelling based on data collected on the high-resolution OHGI setup of the BL44B2 beamline at SPring-8 (Kato & Tanaka, 2016;Kato et al, 2010Kato et al, , 2019Kato & Shigeta, 2020) on diamond and the organic molecular crystals of urea and xylitol.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the measured intensity of OHGI, the precision and accuracy are significantly influenced by XRNU, as described in Section 1. To correct the data for XRNU, correction factors were obtained with ReLiEf (Kato et al, 2019;Kato & Shigeta, 2020) at the incident wavelength and energy threshold that were identical to those used for sample measurement. To investigate for any systematic intensity errors, total-scattering data obtained using the appropriate XRNU correction factors have been examined in terms of ADPs of Si at 100 and 300 K. The ADPs of Si at these temperatures are established from theory and previously reported experiments.…”
Section: Boxcar Refinements In Direct Spacementioning
confidence: 99%
“…However, the flat-field calibration, which needs a uniform reference intensity, has failed to reduce the level further because it is impossible to produce a completely uniform intensity. Recently, Kato et al (Kato et al, 2019;Kato & Shigeta, 2020) have developed a data-driven approach to the problem without using a uniform intensity, which is referred to as ReLiEf (response-to-light effector). The ReLiEf approach has succeeded in reducing the XRNU noise level in MYTHEN modules down to 0.1%, which is equivalent to a dynamic range of 10 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, this dynamic range is significantly reduced by non-uniformity of the X-ray response. Recently, the dynamic range has been largely restored by a statistical approach to the response correction (Kato & Shigeta, 2020). Svane et al (2021) have used the reported image-plate results for diamond as a benchmark to evaluate the data from the MYTHEN detector with the new correction.…”
mentioning
confidence: 99%